(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
The article considers the notion of the concept in its relation to the meaning of the word. Similarities and differences between these two constructs are identified. The dual nature of the concept is discussed. In this article defines cognitive approach, concept and conceptualization. This article determines the basic notion of Cognitive Linguistics. This article dwells upon the basic unit of cognitive linguistics, which is a concept. Firstly, we provide an overview of major scientific works written by foreign linguists who pay attention to special aspects and lines of research. Secondly, we analyse conclusions on modern problems in linguistics that are drawn in cognitological studies conducted since the end of the 20th century. We also touch upon the course and practice of cognitive linguistics while considering the connection between cognition and language.